2008
DOI: 10.1007/s00508-008-1094-2
|View full text |Cite
|
Sign up to set email alerts
|

Die Wirkung von Glycopyrroniumbromid im Vergleich mit Scopolamin-Hydrobromicum beim terminalen Rasseln: Eine randomisierte, doppelblinde Pilotstudie

Abstract: Glycopyrronium bromide given in a dose of 0,4 mg every six hours demonstrated a significant reduction of death rattle compared to scopolamine hydrobromide. Concerning side effects (restlessness, expressions of pain) there was no difference between both substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Past studies differ in their support of glycopyrrolate over other anticholinergic medications such as scopolamine or atropine in reducing secretions (24-27). The largest multicenter study on death rattle treatment is a randomized prospective trial that found no difference in effectiveness among three anticholinergics – scopolamine, atropine, and hyoscine butylbromide (28).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies differ in their support of glycopyrrolate over other anticholinergic medications such as scopolamine or atropine in reducing secretions (24-27). The largest multicenter study on death rattle treatment is a randomized prospective trial that found no difference in effectiveness among three anticholinergics – scopolamine, atropine, and hyoscine butylbromide (28).…”
Section: Discussionmentioning
confidence: 99%
“…Likar et al. () found in favour of the intervention and Heisler et al. () found in favour of placebo, though neither results were statistically significant (Figure ).…”
Section: Resultsmentioning
confidence: 93%
“…The trials comparing an antimuscarinic drug to placebo balanced each other out. Likar et al (2008) found in favour of the intervention and Heisler et al (2013) found in favour of placebo, though neither results were statistically significant ( Figure 2). Furthermore, Hugel et al (2006) found glycopyrrolate superior to hyoscine, whereas Back et al (2001) found the opposite.…”
Section: Pharmacological Treatmentsmentioning
confidence: 85%
See 2 more Smart Citations